Responding to non-salient targets after cues and adaptation – investigating the principle of inverse-effectiveness in psychophysics. - Lau, Wee Kiat. (2013)
The goal of this study was to investigate multisensory processing in the peripheral vision using a multisensory effect called inverse effectiveness (IE). The salience parameter for auditory and visual stimuli used in this study was at the detection threshold subjective to the participant. This parameter was termed non-salient and was used to elicit IE. Multisensory process was hypothesized to occur in the peripheral vision if the non-salient multimodal cues enhanced the judgment of non-salient unimodal targets that were subsequently presented at the cue location, or if judgment to non-salient multimodal targets were unaffected by adaptation. Participants (N = 5) recruited from the university research pool went through a series of psychophysical testing consisting of adaptation and cue conditions. Results showed that the experimental stimuli could not elicit IE because there were no significant changes in reaction times and accuracy. There were also no adaptation aftereffects on the group-level. Thus, both hypotheses could not be tested. However, because an auditory tone improved judgment to visual targets, it was still plausible that multisensory processing could occur in the peripheral vision.